PENERAPAN PRINSIP NON-REFOULEMENT OLEH INDONESIA BERDASARKAN ASEAN FOREIGN MINISTERS MEETING (AMM) - Juliardy, Muhammad Andryan; Saeri, Mhd. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This Indonesia's strategic position makes it one of the countries that refugees who use boats pass through to get to safer locations from their home countries, especially for refugees from the Southeast Asian region in the case of the Vietnamese and Rohingya refugee crises. This research showed that Indonesia became a country that applied the principle of non-refoulement because of the joint pressure that occurred in the ASEAN Foreign Ministers Meeting in discussing refugee issues in the region. Through qualitative methods with data collection techniques using the literature review method at the ASEAN Secretariat Library and the National Library of the Republic of Indonesia by analyzing books, journals, and official documents of the Indonesian state. The author proved that the regime can regulate the behavior of the state in making decisions, Indonesia's joining ASEAN makes Indonesia have to follow the rules or mutual agreements that have been made with other member countries. Keywords: ASEAN, Non-Refoulement, Refugees, Southeast Asia